Distribution of heavy metals and REE in soil from Cameron Highland and Lojing - Mohamed Azlan Yusoof Abdul Haiyoo (2024)
This study investigates the distribution of heavy metals and rare earth elements (REEs) in soil from Cameron Highland and Lojing, two important agricultural and mining regions in Malaysia. Soil samples were collected from various locations across the study area and analyzed for concentrations of heavy metals such as lead (Pb), cadmium (Cd), chromium (Cr), nickel (Ni), as well as REEs including lanthanum (La), cerium (Ce), and gadolinium (Gd). The results revealed spatial variations in the concentrations of these elements, with elevated levels observed in areas affected by human activities such as agriculture, mining, and urbanization. The presence of heavy metals and REEs in soil poses potential risks to human health and the environment, necessitating continued monitoring and management efforts. This study provides valuable insights into the sources, distribution patterns, and environmental implications of heavy metal and REE contamination in soil from Cameron Highland and Lojing, contributing to our understanding of soil quality and land use sustainability in the region. Further research is needed to assess the long-term impacts of soil contamination and develop effective mitigation strategies for safeguarding ecosystem health and human well-being.